Contribution of HRD Practices on Employees’ Commitment: An Observation of Development Banks in Nepal - Chaudhary, Manoj Kumar; Chaudhary, Rajesh Kumar (Nepal Journal of Multidisciplinary Research, 2022)
The dynamics of business environment always poses sever new issues that need to be consider by an organization to be competitive in the business. The human resource development practices can be an instrument to meet this prerequisite. Considering this fact, this study aimed to examine the contribution of HRD practices on the commitment of employees in Nepalese development banks. For this, 320 bankers as respondents are selected from national level development banks with head office based on Kathmandu valley to meet the study objectives. Structured questionnaire as an instrument for data collection based on 5-point Likert scale has been applied. The data are processed and analyzed with use of MS-Excel, SPSS, descriptive, correlation and regression analysis. The findings shows that HRD dimensions has significant positive association and impact on commitment of employees in Nepalese development banks. However, integrated HRD strategies still need to be considered by the development banks for its own effectiveness as exposed by the respondents. Thus, the researchers concludes that HRD practices to make their employees more dedicated and committed as per the dynamics of market then development banks of Nepal should be considered integrated HRD practice as a core value of their banks. Therefore, it is recommended that stakeholders specially executives of banks to put keen attention for framing a suitable HRD strategy for remain competitive.